How Significant The Influance of Financial Performance and Ownership Characteristic to Environmental Cost - Popon Rabia Adawia; Yuli Komalasari; Asriani Natong (Dinasti Publisher, 2023)
This study aims to empirically examine the effect of liquidity, profitability and institutional ownership on environmental costs in Green Industry companies that are registered on the Indonesian Stock Exchange for the 2016-2021 period. The research method is causal associative quantitative. The population is 23 companies that have won green industry awards (PROPER in the Green and Gold category) and the sample is 18 companies for the 2016-2021 period. Samples were taken based on porposive sampling. The dependent variable is environmental cost and the independent variable is liquidity, profitability and institutional ownership. The method used in testing this hypothesis is regression analysis. panel data is processed using eviews 10 software with the t-test then the f-test with a significant level of five percent and the coefficient of determination test. The research results show that the environmental cost is positively and significantly affected by liquidity and profitability. Institutional ownership does not affect and is not significant to environmental costs. The variable that has the most positive effect on environmental cost is profitability. Simultaneous tests of liquidity, profitability and institutional ownership variables have a positive & significant effect on environmental costs in green industry companies that are registered on the Indonesia Stock Exchange for the 2016-2021 period.